English - Despotovic, Aleksa; Milić, Nataša; Stevanović, Goran (Medicinski podmladak, 2023)
Healthcare-associated infections pose a significant risk for patients and a tremendous burden on hospitals and healthcare systems. Because they can significantly affect treatment outcomes, rigorous surveillance and prevention strategies are key interventions against their occurrence. With the growing problem of antimicrobial resistance, further aggravated throughout the COVID-19 pandemic, it has become challenging to find viable therapeutic options. This is particularly the case in intensive care units, where pathogens exhibit the highest resistance rates. Surveillance of healthcare-associated infections comprises continuous monitoring of causative agents, infection types, and the degree of antimicrobial resistance. Such data can inform intervention choices aimed at prevention, but they are critical in selecting the right empirical and targeted treatment. Alongside clinical, epidemiological, and microbiological data, economic analyses are an equally important aspect of healthcare-associated infection surveillance. They provide key insights into the financial burden on hospitals that are responsible for effective preventative measures. Serbia is, according to national data, a country with one of the lowest rates of healthcare-associated infections in Europe, but has one of the highest antimicrobial resistance rates in Europe. These findings point to a need for systemic changes, including more rational antibiotic use and education of the general public, but also of healthcare professionals, with the idea of preventing further progression and impact on treatment outcomes